Perceived Family Support: Emotional, Instrumental, Informational and Award Support in Maintaining the Health of the Elderly in Surabaya, Indonesia: a Descriptive Study - Lembunai Tat Alberta; Rini Ambarwati; Dwi Utari Widyastuti (International Journal of Advanced Health Science and Technology, 2023)
The elderly is a life cycle experienced by every human being and is generally susceptible to diseases, especially degenerative diseases that affect their “health status.” The results showed that the prevalence of chronic diseases in the elderly is increasing over time. In 2015, the elderly morbidity rate was recorded at 28.62% which had an impact on increasing disability and decreasing quality of life. Family support is the attitude, action, acceptance of the family towards its family members in the form of emotional, instrumental, informational, rewarding support. This study was conducted to explain family support for the “health status” of the elderly in the work area of the Pucang Sewu Health Center in Surabaya. Descriptive research method, data collection is carried out directly using questionnaires, descriptive data analysis using percentages. The results showed emotional support was mostly good (70%), instrumental support, informational support and award support were almost entirely good (84%, 86%, and ,90%). This research is useful so that families provide optimal support to the elderly so that the elderly can achieve optimal “health status.” It is recommended to increase family support and the quality of health services so that it is beneficial for the elderly in improving their “health status” and reducing their health complaints.